Effects of Smoking and Cessation on Subclinical Arterial Disease: A Substudy of a Randomized Controlled Trial - Johnson, Heather M. (Public Library of Science, 2012)
BACKGROUND: The mechanisms by which smoking cessation reduces cardiovascular disease risk are unclear. We evaluated longitudinal changes in carotid intima-media thickness among current smokers enrolled in a prospective, randomized smoking cessation clinical trial. METHODOLOGY/PRINCIPAL FINDINGS: Subjects were enrolled in a randomized, double-blind, placebo-controlled trial of 5 smoking cessation pharmacotherapies and underwent carotid ultrasonography with carotid intima-media thickness measurement. Subjects were classified as continuously abstinent (biochemically confirmed abstinence at 6 months, 1 year, and 3 years post-quit attempt), intermittently abstinent (reported smoking at one of the three time points), or smoked continuously (reported smoking at all three time points). The primary endpoint was the absolute change (mm) in carotid intima-media thickness (ΔCIMT(max)) before randomization and 3 years after the target quit date. Pearson correlations were calculated and multivariable regression models (controlling for baseline CIMT(max) and research site) were analyzed. Among 795 subjects (45.2±10.6 years old, 58.5% female), 189 (23.8%) were continuously abstinent, 373 (46.9%) smoked continuously, and 233 (29.3%) were abstinent intermittently. There was a greater increase in carotid intima-media thickness among subjects who were continuously abstinent than among those who smoked continuously (p = 0.020), but not intermittently (p = 0.310). Antihypertensive medication use (p = 0.001) and research site (p<0.001) independently predicted ΔCIMTmax – not smoking status. The greatest increase in carotid intima-media thickness among continuous abstainers was related to increases in body-mass index (p = 0.043). CONCLUSIONS/SIGNIFICANCE: Smoking status did not independently predict ΔCIMT(max); increasing body-mass index and antihypertensive medication use were the most important independent predictors. The rapid reduction in cardiovascular disease events observed with smoking cessation is unlikely to be mediated by changes in subclinical atherosclerosis burden. TRIAL REGISTRATION: ClinicalTrials.gov NCT00332644